Adult Primary Bone Sarcoma and Time to Treatment Initiation: An Analysis of the National Cancer Database. (11th November 2018) - Lawrenz, Joshua M.; Curtis, Gannon L.; Styron, Joseph F.; George, Jaiben; Anderson, Peter M.; Zahler, Stacey; Shepard, Dale R.; Rubin, Brian P.; Nystrom, Lukas M.; Mesko, Nathan W.
Abstract : Objective . The time to treatment interval (TTI), defined as the period from diagnosis to first definitive treatment, has very limited descriptions toward understanding delays in primary bone sarcoma (PBS) care. Our primary goal was to determine the national standard for time to treatment initiation (TTI) in PBS in adults and to identify characteristics associated with TTI variability. Methods . An analysis of the National Cancer Database identified 15, 083 adult patients with PBS diagnosed from 2004 to 2013. Kruskal–Wallis analysis identified differences between covariates regarding TTI and regression modeling identified covariates that independently influenced TTI. Results . The median TTI was 22 days. Approximately 60% of patients were definitively treated in the same center where the index diagnosis was made. Increased TTI was correlated with a transition in care institution (incidence rate ratio (IRR) = 1.89; P < 0.001 ), being uninsured (IRR = 1.36; P < 0.001 ), primary tumor site in the pelvis (IRR = 1.26; P < 0.001 ), Medicaid insurance status (IRR = 1.22; P < 0.001 ), care at an academic center (IRR = 1.14; P < 0.001 ), non-white race (IRR = 1.12; P = 0.002 ), and Medicare insurance status (IRR = 1.08; P = 0.017 ). Decreased TTI was correlated with a diagnosis of chondrosarcoma (IRR = 0.85; P < 0.001 ), having surgery as the index treatment (IRR = 0.88; P < 0.001 ), a primary tumor site of the lower (IRR = 0.91; P = 0.001 ) or upper extremity (IRR = 0.92; P = 0.023 ), and stage II or stage III disease (IRR = 0.91; P = 0.010 ). Conclusions . TTI is associated with tumor, treatment, and socioeconomic and healthcare system characteristics. Transitions in care between institutions are responsible for the greatest increase in TTI. As TTI is more commonly used as a quality metric, physicians need to be aware of the causes for prolonged TTI, as we work to improve national delays in diagnosis and treatment initiation.